Evolving a Business Philosophy - Jones, Manley Howe (Academy of Management Journal, 1960)
Discusses the importance of developing a business philosophy in a corporation. Discussion on corporate decision-making; Community responsibility, corporate goals and other factors in corporate mission statement formation; Details of employee welfare and organizational behavior.